AB0393 Adverse skin reactions in rheumatoid arthritis patients recieving tumor necrosis factor alpha inhibitor – an analysis of data from the slovenian biological registry. (15th June 2017) - Drljača, S; Podovšovnik, A; Rotar, Ž; Hočevar, A; Praprotnik, S; Tomšič, M; ,
Abstract : Background: Paradoxical skin reactions (PSR) are defined as a new onset or worsening of skin conditions during treatment with tumour necrosis factor alpha (TNF-α) inhibitors that generally improve or respond to this therapy. The list of PSR is growing. The most commonly reported are psoriasiform skin eruptions. Objectives: To evaluate the frequency of PSR in the group of rheumatoid arthritis (RA) patients treated with TNF-α inhibitor at the time of development of skin eruption. Methods: We conducted the analysis of the data from the mandatory Slovenian national registry of patients treated with bDMARDs (BioRx.si) which includes spontaneous adverse reaction reports between 01.01.2008–31.05.2016. The analyses were limited to patients with RA. Results: During the observation period, 1, 046 RA (82% female; median (IQR) age at initiation of TNF-α inhibitors 56 (49–63) years) patients treated with TNF-α inhibitors for 3, 140 person years. We identified 14 cases with PSR (71% female, median age (IQR) 45 (53–62)). There were 6 PSR cases on adalimumab, 4 on etanercept, 3 on certolizumab – pegol, and 1 on infliximab. 10 patients developed psoriatic/psoriasiform eruptions, 2 patient leucocytoclastic vasculitis, one had lichen planus, and one undifferentiated skin changes. The incidence rate of new onset of psoriasis in RA patients treated with TNF-α inhibitors was estimated at 3.2 cases/1000 patient-years (95% CI 2.58 to 3.82). The incidence rate of leucocytolastic vasculitis was 0.64/1000 person-years (95% CI 0.36 to 0.92), and of lichen planus 0.32/1000 person-years (95% CI 0.12 to 0.52). Conclusions: The most commonly reported PSR in RA patients treated with TNF-α inhibitor was psoriasiorm PSR, which is in line with published data. Disclosure of Interest: None declared